A Comparative Study of Clinical Trial Recruitment Strategies: Pre-COVID-19 vs. COVID-19 Era (International Journal of Scientific Research in Science and Technology, 2025)
This study investigates the transformation of clinical trial recruitment strategies due to the COVID-19 pandemic. Participant recruitment is a persistent challenge in clinical trials, and the pandemic introduced unprecedented disruptions, necessitating changes to traditional methods. An anonymous online survey was conducted from February to December 2024 with 70 physicians (Principal Investigators, Sub-Investigators, or Clinical Research Coordinators) experienced in clinical trials both before and during COVID-19. The survey assessed recruitment practices across five domains: in-person visits, healthcare provider referrals, physical advertisements, online platforms, and virtual advertisements. Data were analyzed using a chi-square test. Results indicated a significant shift in recruitment practices during the pandemic. There was a notable decrease in in-person recruitment efforts (48.5% pre-COVID vs. 28.5% COVID) and referrals from healthcare providers (41.4% pre-COVID vs. 31.4% COVID). Conversely, the use of online platforms (11.4% pre-COVID vs. 20.0% COVID) and virtual advertisements (5.7% pre-COVID vs. 12.8% COVID) increased. Advertisements in physical locations remained unchanged (15.7%). The chi-square analysis confirmed a statistically significant difference between pre-pandemic and pandemic-era recruitment methods (χ2 = 10.805, d.f. = 4, p value = 0.02884). The study concludes that the COVID-19 pandemic significantly altered clinical trial recruitment strategies, with a marked move from traditional in-person methods to digital approaches like online platforms and virtual advertisements. These adaptations addressed logistical challenges and highlighted the potential for more efficient and inclusive participant engagement, underscoring the need for ongoing innovation in recruitment, particularly through technology.